Surprising abundance of Gallionella-related iron oxidizers in creek sediments at pH 4.4 or at high heavy metal concentrations - Fabisch, Maria; Beulig, Felix; Akob, Denise M.; Küsel, Kirsten (Frontiers in Microbiology, 2013)
We identified and quantified abundant iron-oxidizing bacteria (FeOB) at three iron-rich, metal-contaminated creek sites with increasing sediment pH from extremely acidic (R1, pH 2.7), to moderately acidic (R2, pH 4.4), to slightly acidic (R3, pH 6.3) in a former uranium-mining district. The geochemical parameters showed little variations over the 1.5 year study period. The highest metal concentrations found in creek sediments always coincided with the lowest metal concentrations in creek water at the slightly acidic site R3. Sequential extractions of R3 sediment revealed large portions of heavy metals (Ni, Cu, Zn, Pb, U) bound to the iron oxide fraction. Light microscopy of glass slides exposed in creeks detected twisted stalks characteristic of microaerobic FeOB of the family Gallionellaceae at R3 but also at the acidic site R2. Sequences related to FeOB such as Gallionella ferruginea, Sideroxydans sp. CL21, Ferritrophicum radicicola, and Acidovorax sp. BrG1 were identified in the sediments. The highest fraction of clone sequences similar to the acidophilic ‘Ferrovum myxofaciens’ was detected in R1. Quantitative PCR using primer sets specific for Gallionella spp., Sideroxydans spp., and ‘Ferrovum myxofaciens’ revealed that approximately 72% (R2 sediment) and 37% (R3 sediment) of total bacterial 16S rRNA gene copies could be assigned to groups of FeOB with dominance of microaerobic Gallionella spp. at both sites. Gallionella spp. had similar and very high absolute and relative gene copy numbers in both sediment communities. Thus, Gallionella-like organisms appear to exhibit a greater acid and metal tolerance than shown before. Microaerobic FeOB from R3 creek sediment enriched in newly developed metal gradient tubes tolerated metal concentrations of 35 mM Co, 24 mM Ni, and 1.3 mM Cd, higher than those in sediments. Our results will extend the limited knowledge of FeOB at contaminated, moderately to slightly acidic environments.